Assessment of mother's knowledge towards pregnancy, childbirth, postpartum and essential newborn care in district Solan, HP - Behal, Manisha; Vinayak, Rajeev; Kumar, Arjit (International Journal Of Community Medicine And Public Health, 2018)
Background: Even though the neonatal, maternal and perinatal mortality is declining in our country, still the morbidity and mortality rate is very high. Further improvement is possible by increasing awareness and appropriate practices of mothers towards pregnancy, childbirth, postpartum and essential newborn care. Objective of the study was to assess the knowledge of postnatal mothers regarding pregnancy, childbirth, postpartum and newborn care. These feeding practices were assessed in postnatal mothers, using a structured questionnaire. Methods: Univariate analyses method [such as frequencies, percent distribution, means, and standard deviations (SD)] and Binary Logistic regression method was used for analysis of data with help of analyse-it and SPSS software. Results: Knowledge regarding pregnancy, childbirth and postpartum care: Mean percentage obtained was 68.128% (SD of 18.15). 100% was obtained by only 7 mothers (2.3% of total). Knowledge regarding essential newborn care: Mean percentage obtained was 59.8% (SD of 19.6). 100% was obtained by only 15 mothers (5% of total). A total of 71 mothers failed, constituting 23.7% of total. Education status and parity status both were significantly associated with maternal knowledge regarding pregnancy and postpartum but they do not predict the outcome very well. Conclusions: Postnatal mothers had inadequate knowledge on pregnancy, childbirth, postpartum and newborn care. Therefore educational intervention at multiple levels is required during the period of antenatal, and postnatal visits. Secondly socio-demographic factors- educational status and parity status of postnatal mothers were not associated with maternal knowledge.